Variability in Cardiac Biomarkers during Hemodialysis: A Prospective Cohort Study. (17th December 2020) - Collister, David; Mazzetti, Andrea; Bhalerao, Anuja; Tyrwhitt, Jessica; Kavsak, Peter; Brimble, Kenneth S; Devereaux, P J; Walsh, Michael
Abstract: Background: The effect of hemodialysis on cardiac biomarkers is unclear. We sought to evaluate the degree and causes of intradialytic variability of high sensitivity troponin I (hs-TnI), galectin-3 (gal-3), and heart-type fatty acid binding protein (hFABP). Methods: hs-TnI, gal-3, and hFABP were prospectively measured pre-dialysis and post-dialysis for 1 week every month for 6 months in 178 prevalent adult hemodialysis patients at a single center in Hamilton, Canada. The degree of change from pre-dialysis to post-dialysis for each cardiac biomarker was estimated with multilevel linear regression models. Results: The median change in the concentration of hs-TnI during hemodialysis was −1 ng/L (interquartile range [IQR] −1 to 2 ng/L) while gal-3 and hFABP changed by −36.3 ng/mL (IQR −27.7 to −46.8 ng/mL) and −19.41 ng/mL (IQR −13.61 to −26.87 ng/mL), respectively. The median (IQR) percentage intradialytic changes for hs-TnI, gal-3, and hFABP were 2.6% (−4.4% to 12.5%), −59.8% (−54.7% to −64.8%) and −35.3% (−28.4% to −42.1%), respectively. Ultrafiltration was associated with an increase in concentration of hs-TnI, gal-3, and hFABP (mean 0.99 ng/L, 1.05 ng/mL, and 1.9 ng/mL per L ultrafiltration, respectively, P < 0.001). Both gal-3 and hFABP concentrations decreased in association with the volume of blood processed ( P < 0.001) and with hemodialysis treatment time ( P = 0.02 and P = 0.04) while hs-TnI concentration decreased only in association with hemodialysis treatment time ( P < 0.001). Conclusions: Ultrafiltration volume and hemodialysis treatment time influenced hs-TnI, gal-3, and hFABP concentrations during hemodialysis and should be considered when interpreting their measurement.